An analysis of the capacity system of the Civil and Commercial Code from the perspective of jurisprudence (Nueva Epoca, 2020)
In this work we analyze how the jurisprudence has reflected the changes made in terms of capacity in the five years of the Argentine Civil and Commercial Code.
Keywords: Capacity; Restriction; Inability; Support; Conventionality